2019
DOI: 10.4103/aer.aer_198_18
|View full text |Cite
|
Sign up to set email alerts
|

The effect of forced-air warmer, ondansetron or their combination on shivering in pregnant women coming for elective cesarean section under spinal anesthesia: A prospective, randomized controlled comparative study

Abstract: Context: Perioperative shivering can occur in up to 85% of patients undergoing cesarean section under spinal anesthesia. It has many detrimental effects and disrupts early mother-child bonding. Therefore, it should ideally be prevented by either pharmacologic or nonpharmacological means. Aims: The primary aim of this study was to evaluate the efficacy of intraoperative forced-air warming, ondansetron or their combination in preventing perioperative shivering in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Several studies have reported that preoperative 5-HT 3 receptor antagonists effectively prevent POS after spinal anaesthesia. [8][9][10] However, Rashad and Farmawy did not report any statistically significant differences in the occurrence of shivering between patients administered prophylactic 5-HT 3 receptor antagonists and controls. 11 Previous meta-analyses 12 13 revealed that 5-HT 3 receptor antagonists prevented POS; however, these studies investigated both general and spinal anaesthesia.…”
Section: Open Accessmentioning
confidence: 99%
“…Several studies have reported that preoperative 5-HT 3 receptor antagonists effectively prevent POS after spinal anaesthesia. [8][9][10] However, Rashad and Farmawy did not report any statistically significant differences in the occurrence of shivering between patients administered prophylactic 5-HT 3 receptor antagonists and controls. 11 Previous meta-analyses 12 13 revealed that 5-HT 3 receptor antagonists prevented POS; however, these studies investigated both general and spinal anaesthesia.…”
Section: Open Accessmentioning
confidence: 99%
“…To prevent shivering, pharmacologic drugs, including magnesium sulfate (MS), opioids, α2-agonists, NMDA receptor antagonists, and serotonin 5-HT3 receptor antagonists have been studied (Lema et al, 2017;Liu et al, 2018;Sachidananda et al, 2018). Non-pharmacological therapies such as sheets, radiant warmth, and heated air warmers have also reduced shivering during the intraoperative and perioperative periods (Kiran and Sangineni, 2019). However, there is still a need for alternative therapies that are both effective and safe.…”
Section: Introductionmentioning
confidence: 99%
“…Shivering induces several complications such as interfering with standard monitoring, lactic acidosis, increased carbon dioxide production, and oxygen consumption (6)(7)(8). To date, a variety of pharmacologic agents including magnesium sulfate, opi-oids, α 2 -agonists, N-methyl D-aspartate receptor antagonists, serotonin 5-HT3 receptor antagonist (9)(10)(11), and nonpharmacological interventions such as blankets, radiant heat, and forced air warmers have been used to suppress perioperative shivering (12). However, the problem still exists, and investigation for novel approaches with enough safety and efficacy is strongly recommended.…”
Section: Introductionmentioning
confidence: 99%